The Prevalence of Anxiety, Aggression, and Hostility at Sportswoman: A Study on Boxing - Bugaevsky, Konstantyn; Rybalko, Lina; Muszkieta, Katarzyna (Journal of History Culture and Art Research, 2020)
The study of various types of psychological manifestations in women athletes in age groups, in such a primordially masculine form of martial arts, such as boxing, is very relevant and in demand in the study of modern women’s sports. This article presents the materials of a study devoted to the identification among women boxers of different age groups of the psychological manifestations of aggressiveness, hostility and their types, as well as personal and situational anxiety during the pre-start period of their sports activities, as well as methods and means of overcoming them by athletes. The aim of the article is the presentation and analysis of the identified indicators of the level of aggressiveness, hostility, personal and situational anxiety in athletes of the studied groups. In the study, we used a survey of athletes, according to the method of Bass-Darki (in the modification of A.K. Osnitsky) and the determination of indices of aggressiveness and hostility, to determine the level of aggressiveness (external manifestation) to specific individuals and the hostility (and its orientation toward the external environment) of the person under study; determination of the degree of personal and situational anxiety of athletes in the pre-launch period, using a test questionnaire according to Ch.D. Spielberger (adapted by V.Yu. Khavkin); extended interviewing method. It was reliably established that in all age groups of athletes (n = 127), different increased levels of aggressiveness were present in 40 (31.50%). A high level of hostility was identified in 39 (30.71%) of all athletes. It was also revealed that all high levels of personal anxiety were identified in 41 (32.28%) athletes of all age groups, and in 46 (36.22%) of all athletes - all high levels of situational anxiety. When conducting extended interviews, it was found that all representatives of different age groups have no aggressiveness directed at rivals. The manifestations of verbal aggression predominate, mainly among athletes of puberty and youthful ages. It was determined that personal and situational anxiety prevails among young athletes with a small sports record and an insufficient level of experience in participating in competitions at various levels. It is noted that the level of aggressiveness, hostility, personal and situational anxiety significantly decreases for all athletes, as their sports experience, professional skill, and competitive experience increase.